The Effect of Job Satisfaction and Organizational Commitment on Turnover Intention of Gen Z Employees in Startup Companies - Adi, Bagus Herputranto; Sary, Fetty Poerwita (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The rapid growth of startup companies in Indonesia, driven by digitalization, has positioned Generation Z as a significant part of the workforce. This generation is known for being highly adaptive to technology and strongly oriented toward personal values. However, their high turnover intention presents a major challenge for organizational sustainability. Given their dynamic and selective nature in choosing workplaces, it is crucial to understand the factors influencing their decision to stay. Two key factors are job satisfaction and organizational commitment, which reflect both professional fulfillment and employees’ attachment to their organizations. This study aims to examine the influence of job satisfaction and organizational commitment on turnover intention among Generation Z employees in startup companies. A quantitative approach was used, involving a survey of 280 Gen Z employees from various startups. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that both job satisfaction and organizational commitment have a significant negative effect on turnover intention. In other words, higher levels of satisfaction and commitment are associated with a lower tendency to leave the organization. These findings offer practical insights for startup management in developing more effective retention strategies tailored to Generation Z characteristics. Enhancing job satisfaction and strengthening organizational commitment are key to fostering a stable and productive work environment.